Handbook of advanced materials : enabling new designs - Wessel, James K. (J. Wiley, 2004)
Written to educate readers about recent advances in the area of new materials used in making products. Materials and their properties usually limit the component designer.* Presents information about all of these advanced materials that enable products to be designed in a new way* Provides a cost effective way for the design engineer to become acquainted with new materials* The material expert benefits by being aware of the latest development in all these areas so he/she can focus on further improvements.